Technology as the Panacea for Monitoring of Protected Areas - Shekhar, Shashank; Badola, Ruchi; Pushpanjali, Pragyan (Indian Forester, 2023)
The study highlights the use of technology in ensuring the protection of conservation sites such as forests and heritage sites. In this regard, the research utilizes a qualitative approach to assure that the latest technological advancements have a significant role to play in the monitoring and analysis of protected areas. Thus, the research outlines significant technologies, latest innovations, and upcoming plans to present the importance of technology in improving the monitoring of protected areas. In this context, the research adopts a qualitative research approach by interviewing conservation scientists, forest personnel, environmental researchers and managers of renowned technology companies, manufacturing innovative products that are sold for monitoring protected areas. The findings highlight the efficacy of technology in the conservation of natural resources. Additionally, certain recommendations concerning further improvement of monitoring of protected areas are also provided in the research paper.